Comparison of Intravenous Ketamine and Midazolam Premedication on Emergence Agitation (EA) in Children following Tonsillectomy with or without Adenoidectomy under General Anaesthesia (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Management of emergence agitation (EA) following tonsillectomy with or without adenoidectomy under general anaesthesia in children has been a major challenge for anaesthesiologists.Several medications have been investigated in an attempt to reduce the occurrence and severity of EA.Objectives: The purpose of this study is to determine the effect of premedication with intravenousmidazolam and ketamine on EA following tonsillectomy with or without adenoidectomy under generalanaesthesia in children.Study design: Randomised clinical study.Methods: Sixty children of both sex, American Society of Anaesthesiologists (ASA) physical status I & IIage 5 to 12 years scheduled to undergo elective tonsillectomy with or without adenoidectomy were randomlyassigned into two groups. Patients in group K (n=30) received premedication of intravenous ketamine0.25 mg/kg body weight in 5 ml total volume and in group M (n=30) received premedication 0.1 mg/kgbody weight intravenous midazolam in 5 ml total volume. After completion of surgery patients weretransferred to recovery. Incidences and severity of EA(Paediatric Anaesthesia Emergence Delirium Scale),pain score (Wong-Baker FACES Pain scale) and postoperative nausea and vomiting (PONV) were assessedat admission in the recovery (T0) and in the post anaesthesia care unit (PACU) at 5 min (T5), at 15 min(T15) and at 30 min (T30).Results: Incidences of EA in Group K remained significantly lower than Group M at admission to therecovery and in the PACU at 5 min and 15 min (P